PROBLEMS OF FORMATION AND MANAGEMENT OF COLLATERAL PORTFOLIO OF A COMMERCIAL BANK - Nayimov, Shoxruh (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The collateral portfolio is a critical aspect in the risk management strategies of commercial banks. This article delves into the challenges that banks face in forming and managing a collateral portfolio, considering global practices and specific contextual constraints such as regulatory framework, market volatility, and technological aspects. Drawing from existing literature and empirical evidence, this paper offers recommendations tailored to the banking industry in Uzbekistan.